Contextual English Learning to Empower Nurul Huda Islamic Boarding School Students in Improving Daily Conversation Skills - Eka Agustina; Muhamad Ihwannudin; Muhamad Muklas (English Education Program, Education Faculty, Universitas Nurul Huda, 2026)
This research was carried out to address the low oral communication skills of students in English at the Nurul Huda Islamic Boarding School, particularly in the context of everyday conversation needed for global interactions. This problem arose because previous learning focused more on grammar theory and vocabulary memorization without providing authentic contexts for use. This activity aimed to empower students through the implementation of contextual English learning that emphasizes direct language use in real-life situations at the Islamic boarding school. The methods used included qualitative descriptive method, developing materials based on students' daily situations, interactive training through role-plays and thematic dialogues, and evaluation through performance observation and assessment of communication practices. The results of the activity demonstrated improvements in students' speaking fluency, communication confidence, and choice of context-appropriate expressions. Furthermore, the contextual approach proved more effective and relevant to their learning environment, although ongoing mentoring was still needed to ensure consistency of practice. Overall, this program successfully improved students' communication competencies while strengthening a culture of practical language learning at the Islamic Boarding School.